Diversity of DNA replication in the archaea - Ausiannikava, Darya; Allers, Thorsten (MDPI, 2017)
DNA replication is arguably the most fundamental biological process. On account of their shared evolutionary ancestry, the replication machinery found in archaea is similar to that found in eukaryotes. DNA replication is initiated at origins and is highly conserved in eukaryotes, but our limited understanding of archaea has uncovered a wide diversity of replication initiation mechanisms. Archaeal origins are sequence‐based, as in bacteria, but are bound by initiator proteins that share homology with the eukaryotic origin recognition complex subunit Orc1 and helicase loader Cdc6). Unlike bacteria, archaea may have multiple origins per chromosome and multiple Orc1/Cdc6 initiator proteins. There is no consensus on how these archaeal origins are recognised— some are bound by a single Orc1/Cdc6 protein while others require a multi‐ Orc1/Cdc6 complex. Many archaeal genomes consist of multiple parts—the main chromosome plus several megaplasmids—and in polyploid species these parts are present in multiple copies. This poses a challenge to the regulation of DNA replication. However, one archaeal species (Haloferax volcanii) can survive without replication origins; instead, it uses homologous recombination as an alternative mechanism of initiation. This diversity in DNA replication initiation is all the more remarkable for having been discovered in only three groups of archaea where in vivo studies are possible.